The Current Working Conditions in Ugandan Apparel Assembly Plants - Mike Tebyetekerwa; Nicholus Tayari Akankwasa; Ifra Marriam (Elsevier, 2017)
Background: The present rapid shift of industrialization from developed to developing countries requires developing countries to understand issues related to work organization, management, and working conditions. There are many factors slackening production, of which working conditions is part. A complete inquiry into the workers' working conditions can enable managements to reduce risks in the workplaces and improve productivity. Understanding and awareness of the benefits of workplace research and a probe into the working conditions in the Ugandan apparel assembly plants are urgently required. Methods: A total of 103 (70 women and 33 men) workers from five different plants were interviewed. Together with the top management of various plants, questionnaires about the workers' opinions of their physical working conditions were prepared. Data was collected using two methods: (1) questionnaire; and (2) observation of the workers during their work. Results: The results indicated that poor plant working conditions were mainly contributed by the workers' social factors and the management policies. Conclusion: The government, together with the management, should work to improve the working conditions in the apparel assembly plants, as it greatly affects both. Keywords: apparel assembly plants, ergonomics, musculoskeletal disorders, Uganda, working conditions